3x squared - (3x) squared = 0
That is 1/9x2
This is impossible as the variables are different
x2 * -3x = -3x3
5x2 + 3x + 8x2 = 13x2 + 3x = x(13x + 3)
8x to the second power times 3x to the second power (8x)2 + (3x)2 = 64x2 + 9x2 = 73x2 is one possibility, except the problem called for multiplication which would make the answer 64x squared times 9x squared = 576x to the fourth power It could also be read this way: 8x squared times 3x squared equals 24x to the fourth power. I wish my computer would do those cool little twos.
3x2 can be called "three times x squared", "three x squared", or "three times x to the power of two".
3x squared - (3x) squared = 0
Assuming your quesiton is Multiply x times 3x times 4, the answer would be 3x squared times 4.
Oh, dude, you're hitting me with some math here. So, when you multiply 2x squared by 3x squared, you just multiply the numbers (2 * 3 = 6) and add the exponents (2 + 2 = 4), giving you 6x to the power of 4. It's like algebra on steroids, man.
That is 1/9x2
(3x)(x2) = 3x3.Think of this as (3x1)(1x2). First multiply the numbers: (3)(1) = 3. next multiply the variables: (x1)(x2) = x1+2 = x3 (when you multiply powers with the same base, add the exponents)
2
3x^2 + 6
0.3 to the 3rd power is calculated by multiplying 0.3 by itself three times. This results in 0.3 x 0.3 x 0.3, which equals 0.027. This can also be expressed as 27/1000 or 2.7%.
This is impossible as the variables are different
x2 * -3x = -3x3